Fracturas faciales en pacientes menores de veinte años atendidos en la unidad de cirugía maxilofacial y estomatología del hospital universitario San Vicente de Paúl y la facultad de odontología de la Universidad de Antioquia entre los años 1998 y 2007 (2010)
ABSTRACT: The purpose of this study was to determine the incidence of facial bone fractures in patients under the age of twenty years of age admitted at the Department of Maxillofacial Surgery and Stomatology at Hospital Universitario San Vicente de Paúl and the University of Antioquia, Medellín, by means of a descriptive retrospective analysis. Methods: six hundred fifty-one patients younger than 20 years f age who were treated for a total of 1173 facial bone fractures during a ten-year period between 1998 and 2007, were studied by age, gender, type and common locations of the fractures, etiology of the injury, method of treatment, associated injuries, and the length of hospitalization. The patients were divided into four different age groups. Results: it was found that the majority of facial fractures are found in males. Motorcycle accidents and falls were the two main causes of facial bone fractures in all age groups. The mandibular condyle region was the major injured site followed by fractures of the parasymphysis, and Le Fort III type was the least common fracture. The most common treatment approach used was the combined therapy. Conclusion: these results document that the etiological characters and incidence of facial bone fractures in pediatric patients increased with age. The differences observed should be taken into consideration in studies concerning facial fractures in pediatric patients.